Employment of Tuberculostasis in Serum-Agar Medium for the Study of Production and Activity of Mycobactin - Kochan, Ivan (1971)
Mycobactin (M), an iron-chelating product of tubercle bacilli, neutralized serum tuberculostasis by removing growth-essential iron from transferrin (Tr) and supplying the metal to the bacteria. The competition for iron between Tr and M has been demonstrated by the agar-plate diffusion test. This test is suitable not only for the study of Tr-iron-M interplay but also for the evaluation of serum tuberculostasis. Extremely poor solubility of M in water and consequently its association with lipoidal cell wall of tubercle bacillus was overcome by the use of water-dispersible and surface-active Tween 80. The addition of Tween 80 to culture media insured the presence of M in spent media; otherwise M was extracted from bacillary cells with a solution of Tween 80 or a mixture of ethanol and Tween 80. Although M was produced irrespective of the amount of iron present in culture medium, its production in iron-poor medium was more prolific than in iron-rich medium. M extracted from BCG or H(37)Rv cells neutralized serum tuberculostasis as effectively for the homologous as for heterologous strains. However, the extract of virulent bacilli was much more active in the neutralization than similar extract prepared from attenuated cells; whether this difference is of quantitative or qualitative nature remains to be determined.